2014
DOI: 10.1111/imm.12273
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of the endogenous interferon ligand–receptors in type I and type II interferons response

Abstract: SummarySeparate ligand-receptor paradigms are commonly used for each type of interferon (IFN). However, accumulating evidence suggests that type I and type II IFNs may not be restricted to independent pathways. Using different cell types deficient in IFNAR1, IFNAR2, IFNGR1, IFNGR2 and IFN-c, we evaluated the contribution of each element of the IFN system to the activity of type I and type II IFNs. We show that deficiency in IFNAR1 or IFNAR2 is associated with impairment of type II IFN activity. This impairment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…To sustain the expression of inflammation genes, type I IFNs can act in an autocrine loop by binding a heterodimeric complex of the IFNAR1 and IFNAR2 on the cell surface (29). IFNAR1/2 activation initiates a signaling cascade through the Janus kinase and signal transducer and activator of transcription pathway that induces the transcription of hundreds of ISGs (30, 31).…”
Section: Resultsmentioning
confidence: 99%
“…To sustain the expression of inflammation genes, type I IFNs can act in an autocrine loop by binding a heterodimeric complex of the IFNAR1 and IFNAR2 on the cell surface (29). IFNAR1/2 activation initiates a signaling cascade through the Janus kinase and signal transducer and activator of transcription pathway that induces the transcription of hundreds of ISGs (30, 31).…”
Section: Resultsmentioning
confidence: 99%
“…Unlike IFN-γ, which signals through its unique receptor, all type I interferons signal through the IFN-α receptor 1 (IFNAR1) and IFN-α receptor 2 (IFNAR2) [ 1 ]. Although signaling occurs through different receptors, lack of IFNAR can lead to a diminished IFN-γ signaling pathway, implicating IFNAR in regulation of IFN-γ responsiveness [ 31 ]. To address whether the lack of STAT1 induction in TL-1 cells is specific to IFN-γ or a result of diminished IFNAR-mediated signaling, we assessed the ability of TL-1 cells to respond to IFN-β.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we demonstrate that the lack of IFN-γ responsiveness is not due to defects in the type I interferon signaling pathway ( Fig 4 ). Deficiency in the type I interferon receptors IFNAR1 and IFNAR2 has been shown to dampen IFN-γ signaling [ 31 ]. However, we found that TL-1 cells robustly induce p-STAT1 in response to IFN-β treatment ( Fig 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, increased mRNA expression levels of IFNGR 1 and IFNGR 2 were observed in the pituitary following treatment with IFN-γ. The IFN-γ ligand is a dimmer and binds to a heterodimer receptor, which activates the signal transduction cascades and results in the dimerization of the signal transducers and activators of gene transcription [ 7 , 8 , 47 ]. In our research, the combination of endogenous IFN-γ ligand and the pre-assembled up-regulated receptor complex activated the relevant signaling pathways and led to increased FSH-β expression at the transcription level, promoting the synthesis and secretion of FSH.…”
Section: Discussionmentioning
confidence: 99%